Maternal Smoking during Pregnancy and its effects on Neural Tube Defects - Elahi, Zeynab; Hassanzadeh, Farideh; Satarzadeh, Mohammad (Iranian Journal of Child Neurology, 2024)
Objectives Maternal smoking is a potent teratogen among congenital malformations, however its role in the development of Neural Tube Defects (NTDs) is still unclear. In this systematic review, we intend to further investigate the interaction of smoking during pregnancy and the incidence of NTDs. Materials & Methods This article was written according to PRISMA criteria from February 2015 and August 2022. After examining the four stages of PRISMA criteria, we selected clinical articles. These articles were selected from PubMed, Scopus and Google scholar (for results follow-up) databases. We gathered NTDs effect and types, smoking type and habit of parents, from neonates. Results Eventually, 8 articles were included by two separated authors, Smoking was associated with an increase NTDs in the population of pregnant mothers and also among children whose fathers smoked. The main side effects that were considered to be the cause of NTDs besides smoking were alcohol and BMI (18.5-24.9). Smoking also affects the level of folic acid as a substance with an essential role that affects the closure of the neural tube. folic acid available to infants changing along with the level of other blood elements such as zinc, that necessary prevent for NTDs condition. Conclusion Parental smoking can be considered as one of the strong teratogens in the occurrence of NTDs. Smoking, whether active or passive by the mother, or by the father, is associated with the occurrence of NTDs, In order to reduce the prevalence this disorder, we advise pregnant mothers and neonate’s fathers to quit smoking.